2
Объяснение:
3x-5=2(x+1)+x
3x-5=2x+x+2
3x-5=3x+2
3x-3x-5+2=0
-3=0 - невозможно
2) и 3)
1) 2(х-5)=3(х+1)
2(х-5)-3(х+1)=0
2х-10-3х-3=0
-х=30
х=-30
2) 3х-5 =2(х+1)+х
3х-5=2х+2+х
3х-2х-х= 2+5
0х=10
не имеет корней, т.к. на 0 делить нельзя
3)5-(х+1)=3х-4(х-1)
5-х-1=3х-4х+4
-х-3х+4х=4-5
0х=-1
не имеет корней
4)3х+5(2-3х)=3х-3
3х+10-15х=3х-3
3х-15х-3х=-3-10
-15х=-13
х=-13/-15
2
Объяснение:
3x-5=2(x+1)+x
3x-5=2x+x+2
3x-5=3x+2
3x-3x-5+2=0
-3=0 - невозможно
2) и 3)
Объяснение:
1) 2(х-5)=3(х+1)
2(х-5)-3(х+1)=0
2х-10-3х-3=0
-х=30
х=-30
2) 3х-5 =2(х+1)+х
3х-5=2х+2+х
3х-2х-х= 2+5
0х=10
не имеет корней, т.к. на 0 делить нельзя
3)5-(х+1)=3х-4(х-1)
5-х-1=3х-4х+4
-х-3х+4х=4-5
0х=-1
не имеет корней
4)3х+5(2-3х)=3х-3
3х+10-15х=3х-3
3х-15х-3х=-3-10
-15х=-13
х=-13/-15